Avaliação de serviços de atenção básica: atualização e validação do instrumento QualiAB - Zarili, Thais Fernanda Tortorelli [UNESP] (2015)
The Primary Health Care (PHC) has a strategic function in the construction of a universal health care system. The quality of services is now one of the major challenges to be faced by PHC, which highlights conducting evaluation surveys and quality monitoring as part of the field of management and planning in health. The QualiAB tool is an instrument that evaluates the organization of the work process through care indicators' and management PHC units. It was developed and applied in 2007 and reapplied in 2010 in São Paulo state. Although it has demonstrated reliability and validity, it requires periodic updates compromised to the continuous increase in quality. The aim of this study is to analyze comparatively between 2007 and 2010 applications and to describe and analyze the process of updating and validation of this tool as a product having an updated version and validated for national implementation. The methodology consists of sequential steps and iterative: comparative analysis between 2007 and 2010 applications; update issues, criteria, standards and indicators for peer review to define a draft, which was submitted to the pretest in 30 selected services; new review with obtaining a second version which was submetted consultation by group of experts and pilot application in a region of the São Paulo state; data analysis to define the version for national implementation. As a result is in the comparative analysis of the previous applications 5 indicators of Management and 17 Assistance, as well as the set of respondents units had p< 0.05. We obtained initially an instrument peer reviewed (QAB1) used for consultation in the pre-test with 111 questions, 17 of which are descriptive and 94 scored. The second version (QAB2) has 126 questions, with 21 questions and 105 descriptive scored and was evaluated by a group of experts through modified Delphi technique, held in two rounds. The results were compared with a pilot application in a ...